Language and communication issues in the education of Africa - Mhute, Isaac (Nova Publishers, 2022)
This book comes at a time when Africa is attempting to reinvigorate itself, putting itself on a path for continued stability and economic growth. These reformations have been more pronounced in the educational system, as educational institutions in Africa try to find new ways of making themselves more relevant and repositioning themselves to respond to numerous problems confronting the continent. The book tackles wide-ranging and topical issues that include the decolonisation of education, the implications of COVID-19 on institutions of higher learning, pandemic discourse and education in Africa, gender issues in education, indigenous knowledge systems, transnational education (TNE) partnerships and distance learning issues. This book is a timely contribution that includes views from seasoned scholars from different parts of the continent, such as Ghana, Uganda, Nigeria, Zimbabwe, South Africa and Kenya, as well as the African Diaspora such as Germany and the United Kingdom. The book will be a useful resource for educators, policymakers and students in various sub-fields related to education.